DEVELOPMENT OF A COLLABORATIVE-BASED INTERACTIVE STORYTELLING MODEL ON SKILLS SPEAKING OF GRADE IV ELEMENTARY SCHOOL STUDENTS - Istikhoroh Nurzaman; Dwi Alia; Pidi Mohammad Setiadi; Liz Erlyna; Iis Haerunisa (Universitas Majalengka, 2023)
The Android-based Interactive Storytelling Model Research is the initial research that has been conducted, and it concluded that the model used can stimulate students' speaking skills. However, besides that, this research shows that there are deficiencies, namely the limitations of teachers and students in operating Android. Complementing the lack of research that has been done, this research was carried out, which aims to develop a Collaborative-based Interactive Storytelling Model. This study aims to develop a learning model that can stimulate students' speaking skills with the help of presenting practitioners. This research was carried out by going through the stages of the EDR development research procedure proposed by McKenny & Reeves. The research stages that have been carried out are 1) the analysis and exploration stage, 2) the design and construction stage, and 3) the evaluation and reflection stage. The data were obtained from interviews, literature studies, and field trials tested on fourth-grade students at SDN 3 Karangsambung. The final result of this research is to produce a storytelling guidebook product based collaboratively with the image castle community and have gone through the trial phase twice. Based on the expert assessment results and the trials that have been carried out, this interactive storytelling model is declared feasible for use in learning. Penelitian Model Interactive Storytelling berbasis Android merupakan penelitian awal yang telah dilakukan dan menghasilkan kesimpulan bahwa model yang digunakan dapat menstimulus keterampilan berbicara siswa. Namun di samping itu, penelitian tersebut menunjukan adanya kekurangan yaitu keterbatasan guru dan siswa dalam mengoperasikan android. Untuk melengkapi kekurangan penelitian yang telah dilakukan, maka dilakukan penelitian ini yang bertujuan mengembangkan Model Interactive Storytelling berbasis Kolaboratif. Penelitian ini bertujuan untuk mengembangkan model pembelajaran yang mampu memberikan stimulasi keterampilan berbicara siswa dengan bantuan menghadirkan praktisi. Penelitian ini dilaksanakan dengan melalui tahapan prosedur penelitian pengembangan EDR yang dikemukakan oleh McKenny & Reeves. Adapun tahapan penelitian yang telah dilaksanakan, yaitu: 1) Tahap analisis dan eksplorasi, 2) Tahap desain dan kontruksi, dan 3) Tahap evaluasi dan refleksi. Data diperoleh dari hasil wawancara, studi literatur, dan uji coba dilapangan yang diujikan pada siswa kelas IV di SDN 3 Karangsambung. Hasil akhir dari penelitian ini menghasilkan produk buku panduan bercerita berbasis kolaboratif bersama Komunitas Kastel Imaji dan telah melalui tahap uji coba sebanyak dua kali. Berdasarkan hasil penilaian ahli dan hasil uji coba yang telah dilaksanakan, model Interactive Storytelling ini dinyatakan layak untuk digunakan dalam pembelajaran.